Optimalisasi Citra MRI Ankle Joint Dengan Penerapan Oblique 3D FSPGR Di Instalasi Radiologi RSUD Dr. Moewardi - Dewa Ayu Made Pramita Dewi; I Putu Eka Juliantara; I Putu Sugiartha (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
MRI (Magnetic Resonance Imaging) examination becomes tool diagnostic important in evaluation the soft tissue anatomy of the human body. MRI examination of the ankle joint role crucial in detect soft tissue impingement in the ankle joint. Fast Spoiled Gradient Echo (FSPGR) is an MRI method with high sensitivity in diagnose soft tissue problems in the ankle joint. Ankle joint MRI protocol at RSUD Dr. Moewardi uses several types of sequences with addition 3D sequences but not routinely. This study aims to examine the use of the 3D FSPGR oblique sequence in MRI ankle joint, while comparing it with the Sagittal T1 FSE and Sagittal FSE STIR sequences. This quantitative study involved 5 people to compare imaging 3D oblique FSPGR, sagittal T1 FSE and sagittal FSE STIR sequences. Analysis was carried out using the intraclass correlation coefficient (ICC) test, Friedman test, and Kruskal Wallis test. The results study showed there is difference information MRI ankle joint anatomy with oblique 3D FSPGR, sagittal T1 FSE, and sagittal FSE STIR sequences (p-value = 0.000). Test Kruskal Wallis show sequence 3D FSPGR and sagittal T1 FSE produce imaging different on every type anatomy (p-value= 0.045; 0.020), whereas Sagittal FSE STIR sequence shows results No different significant (p-value= 0.065. 3D oblique sequence of FSPGR is proven effective show anatomy ankle joint and posterior talofibular ligament.